Factors associated with platelet yield in single-donor platelets - S Maneewan (Journal of Health Science and Medical Research (JHSMR), 2004)
Objective: To identify factors associated with platelet yield in single-donor platelets. Material and Methods: Two-hundred donors who underwent plateletpheresis by an intermittent-flow automatic blood cell separator from November 2001- October 2003 in Songklanagarind Hospital were studied. Results: Platelet yield had a positive correlation with prepheresis platelet count ( r = 0.5133,  p  <  0.0001 ), total volume processed ( r = 0.3122,  p  <  0.0001 ), age ( r = 0.1570, p = 0.0264 ), procedure time ( r = 0.1437, p = 0.0424 ), and a negative correlation with prepheresis hematocrit  (r = -0.2035, p = 0.0038) . Weight, height and gender had no significant correlations ( p  >  0.05 ). From multivariate analysis, only two variables, prepheresis platelet count and total volume processed, were statistically significantly ( p <  0.0001 ) related to platelet yield. Higher values of these variables corresponded to a higher platelet yields. Conclusion: Platelet yield depends on prepheresis platelet count and total volume processed. Therefore these variables can be used for selecting the donors for plateletpheresis and can be developed to standardize plateletpheresis in the future.